Burdens of history : British feminists, Indian women, and imperial culture, 1865-1915 - Burton, Antoinette M., 1961- (Chapel Hill : University of North Carolina Press, 1994)
In this study of British middle-class feminism in the late nineteenth and early twentieth centuries, Antoinette Burton explores an important but neglected historical dimension of the relationship between feminism and imperialism. Demonstrating how feminists in the United Kingdom appropriated imperial ideology and rhetoric to justify their own right to equality, she reveals a variety of feminisms grounded in notions of moral and racial superiority.
The politics of recovery: historicizing imperial feminism, 1865-1915 -- Woman in the nation: feminism, race, and empire in the "National" culture -- Female emancipation and the other woman -- Reading Indian women: feminist periodicals and imperial identity -- The White woman's burden: Josephine Butler and the Indian campaign, 1886-1915 -- A girdle round the earth: British imperial suffrage and the ideology of global sisterhood -- Representation, empire, and feminist history.
Includes bibliographical references (pages 271-294) and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
eBooks on EBSCOhost
Keywords: Feminism -- Great Britain -- History; Feminists -- Great Britain -- Attitudes -- History; Women -- India -- History; Imperialism -- History; Electronic books; Feminism -- history; Women -- history; Colonialism -- history; Féminisme -- Grande-Bretagne -- Histoire; Féministes -- Grande-Bretagne -- Attitudes -- Histoire; Femmes -- Inde -- Histoire; Impérialisme -- Histoire; Livres numériques.; e-books.; SOCIAL SCIENCE -- Feminism & Feminist Theory; Feminism; Feminists -- Attitudes; Imperialism; Women; Great Britain; India; Feminismus; Imperialismus; Großbritannien; Indien; Feminisme; Kolonialisme; Geschichte 1865-1915.; History